2004
DOI: 10.1111/j.1520-037x.2004.03594.x
|View full text |Cite
|
Sign up to set email alerts
|

Atorvastatin Reduces Remnant Lipoproteins and Small, Dense Low‐Density Lipoproteins Regardless of the Baseline Lipid Pattern

Abstract: Elevated plasma levels of remnant lipoproteins and small, dense low-density lipoprotein (LDL) particles increase the risk of atherosclerosis. This prospective, placebo-controlled, crossover trial evaluated the effect of atorvastatin on various lipid parameters including remnant lipoproteins and small, dense-LDL cholesterol levels. Forty-five subjects were enrolled in the study. These subjects fell into three distinct lipid patterns: atherogenic dyslipidemia, isolated hypercholesterolemia, and mixed dyslipidemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
3

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 48 publications
(55 reference statements)
1
4
0
3
Order By: Relevance
“…With respect to the sd-LDL cholesterol levels in the present study, the individualized starting doses of atorvastatin had a strong effect on the mean LDL particle size, and markedly reduced the sd-LDL cholesterol levels with all of the doses. These findings are in agreement with previous small studies, which have shown that atorvastatin is effective in reducing the levels of sd-LDL cholesterol particles and improving the abnormal LDL particle distribution in patients with or without diabetes 27,28 . Notably, the changes in the sd-LDL cholesterol levels were proportionately greater based on the baseline LDL cholesterol levels, which supports the idea that a higher starting dose based on a treatment algorithm was advantageous for patients with type 2 diabetes [9][10][11]26 .…”
Section: Discussionsupporting
confidence: 93%
“…With respect to the sd-LDL cholesterol levels in the present study, the individualized starting doses of atorvastatin had a strong effect on the mean LDL particle size, and markedly reduced the sd-LDL cholesterol levels with all of the doses. These findings are in agreement with previous small studies, which have shown that atorvastatin is effective in reducing the levels of sd-LDL cholesterol particles and improving the abnormal LDL particle distribution in patients with or without diabetes 27,28 . Notably, the changes in the sd-LDL cholesterol levels were proportionately greater based on the baseline LDL cholesterol levels, which supports the idea that a higher starting dose based on a treatment algorithm was advantageous for patients with type 2 diabetes [9][10][11]26 .…”
Section: Discussionsupporting
confidence: 93%
“…Treatment with atorvastatin resulted more frequently in a beneficial effect (nineteen studies) [26,30,[54][55][56][57][58][59][60][61][62][63][64][65][66][67][68][69][70] than not (eleven studies) [36,46,[71][72][73][74][75][76][77][78][79] and this has been confirmed at different doses and in a wide-range of different categories of patients: with hypercholesterolaemia [60,63,64,70], with hypertriglyceridemia [65], with combined [30,55,56,58,59,67,69] or familial combined hyperlipidemia [26], with familial hypercholesterolemia [54,61], with type 1 [68] and 2 diabetes [57,58,…”
Section: Atorvastatinmentioning
confidence: 99%
“…Generally, with a 1% decrease in cholesterol levels, a 1% reduction in coronary risk is achieved. [42][43][44][45] The particular properties of statins were discovered in a metanalysis of 51 studies evaluating the efficacy of hypocholesterolemic therapy, statins appearing to be more effective than other hypocholesterolemic drugs. 46 However, as these drugs have no effect on Lp(a)-derived cholesterol, subjects with markedly higher overall Lp(a) levels should be carefully evaluated for the effects of statins.…”
Section: S H O U L D W E T R E a T H Y P E R L I P E M I A I N T H mentioning
confidence: 99%